The Influence of Motivation and Learning Behavior on Learning Achievement During New Normal Learning - Artanti, Vania Fredline; Rimadias, Santi (The Eastasouth Management and Business, 2025)
This study examines the influence of intrinsic and extrinsic motivation, as well as learning behavior, on student learning achievement during the new normal learning period. Using a Structural Equation Modeling approach with SmartPLS, the study finds that both intrinsic and extrinsic motivation significantly influence learning achievement. Learning behavior significantly mediates the effect of extrinsic motivation but not intrinsic motivation. The findings suggest that enhancing extrinsic motivational factors and encouraging effective learning behaviors can improve student performance in hybrid learning environments.